2018
DOI: 10.1063/1.5018930
|View full text |Cite
|
Sign up to set email alerts
|

Validation of gyrokinetic simulations with measurements of electron temperature fluctuations and density-temperature phase angles on ASDEX Upgrade

Abstract: Measurements of turbulent electron temperature fluctuation amplitudes, δT e⊥ /Te, frequency spectra and radial correlation lengths, Lr(T e⊥ ), have been performed at ASDEX Upgrade using a newly upgraded Correlation ECE diagnostic in the range of scales k ⊥ < 1.4cm −1 , kr < 3.5cm(k ⊥ ρs < 0.28 and krρs < 0.7). The phase angle between turbulent temperature and density fluctuations, αnT , has also been measured by using an ECE radiometer coupled to a reflectometer along the same line of sight. These quantities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 50 publications
3
46
1
Order By: Relevance
“…The period of the time average only begins after initial transients have died off in the simulation, and the effect of E × B shear has been fully realized. Figure 4 shows the time trace from the heat flux ‡ Note that the uncertainty in Pe quoted in this study (18 %) is larger than that in Reference [34] (14 %). This is due to additional uncertainty discovered in the routines that calculate the radiated power profiles since the publication of that study.…”
Section: Nonlinear Heat Flux Comparisonmentioning
confidence: 65%
See 3 more Smart Citations
“…The period of the time average only begins after initial transients have died off in the simulation, and the effect of E × B shear has been fully realized. Figure 4 shows the time trace from the heat flux ‡ Note that the uncertainty in Pe quoted in this study (18 %) is larger than that in Reference [34] (14 %). This is due to additional uncertainty discovered in the routines that calculate the radiated power profiles since the publication of that study.…”
Section: Nonlinear Heat Flux Comparisonmentioning
confidence: 65%
“…Note that the validation study presented in this work is for the same plasma discharge used in the validation study in Reference [34]. The work here, however, focuses on a different radial location and utilizes the perturbative thermal diffusivity as an additional validation constraint (for the first time on ASDEX Upgrade), instead of fluctuation measurements.…”
Section: Validation Of Local Ion-scale Nonlinear Genementioning
confidence: 99%
See 2 more Smart Citations
“…We find that the CECE channel comb significantly improves the reliability of the radial alignment between radiometer and reflectometer. All quantities have been measured simultaneously at the same radius in dominantly electron heated L-mode plasma and have been compared directly to nonlinear ion scale GK simulations [7]. It is found that both electron and ion heat flux can be matched, along with α nT and L r (T e⊥ ), however δT e⊥ /T e is higher in the simulations than measured.…”
Section: Introductionmentioning
confidence: 99%